WORKING WOMEN BEHAVIOR ON CERVICAL CANCER AS PARTICIPANTS OF NATIONAL HEALTH INSURANCE - Awang Saputra; Suginarti Suginarti; Ahmad Faridi (STIKes Hang Tuah Pekanbaru, 2020)
Reproductive health maintenance too early detection as possible arises diseases. Working women as civil servants have received as participants of national health insurance improving the quality of healthy, especially low awareness of cervical cancer inspection caused many factors. Cervical cancer is cancer that has a precancerous stage it can be detected by the Pap smear method. The objective of this research to identify factors related to the early detection behavior of cervical cancer with pap smear methods on working women as participants of national health insurance at Serang City. The research method used is quantitative descriptive with correlation analysis. The sample population of 158 working women’s by random sampling. The instrument used questionnaires consisting of 31 questions. The statistical test used is the chi-square test. The data were analyzed by univariate, bivariates, and multivariate analysis. There were 6 factors working woman related to early detection of cervical cancer inspection behaviour are: knowledge (p= 0.046), self-motivation (p= 0.004), age (p= 0.007), length of marriage (p= 0,000), number of children (p= 0.017), and education (p= 0,000). Knowledge, self-motivation, ages, length of the marriage, number of children and education are factors that can influence early detection of cervical cancer inspection the working women as participants of national health insurance.